Youtube videos as an ınformation source about aerobic exercise in rehabilitation of lung cancer - Kocamaz, Deniz; Demircioğlu Karagöz, Arzu; Atasavun Uysal, Songul; Kocamaz, Deniz (SAGE Publications Inc., 2025)
Objective: The internet has become a preferred source for obtaining information about diagnostic and treatment methods related to health issues. This study aims to investigate whether aerobic exercise videos on the YouTube platform are an excellent source for lung cancer patients. Methods: The keywords, “lung cancer and exercise,” “lung cancer and physical activity,” and “lung cancer and rehabilitation” were used to identify videos on YouTube on 27 to 28 May 2023. We recorded the characteristics of the videos, including the number of views, duration, days since upload, and the number of likes and dislikes. The Global Quality Scale and the modified DISCERN questionnaire were used to assess the quality and reliability of videos. Results: 150 videos were evaluated. 12 of 150 videos met the eligibility criteria. Lung cancer and aerobic exercise in rehabilitation videos were most commonly uploaded by health organizations and patients. Videos had a median of 3300 views. We assessed videos for user-focused video quality using the DISCERN instrument and found that the average total score was 3 (range 2-5). Inter-observer agreement was 0.89 and 0.91 for DISCERN and GQS scored, respectively. Significance of Results: The results show that YouTube can be a preferred, easy, and inexpensive way to access aerobic exercise modalities, which are the basic rehabilitation steps for lung cancer patients. Experts recommend increasing the number of high-quality videos explaining the exercises. To fill this gap, healthcare professionals and organizations can take an active role in planning, producing, or ensuring reliable content. Collaborations with medical institutions and physiotherapists could further ensure that patients have access to accurate and effective exercise guidance, ultimately improving rehabilitation outcomes. © The Author(s) 2025.
Keywords: exercise; lung cancer; physical activity; rehabilitation; YouTube